2002 IEEE Ultrasonics Symposium, 2002. Proceedings.
DOI: 10.1109/ultsym.2002.1192578
|View full text |Cite
|
Sign up to set email alerts
|

High frequency ultrasound with an eigen-decomposition filter to assess the effect of laser cyclophotocoagulation treatment on blood flow

Abstract: We use high frequency ultrasound to assess the effect of laser cyclophotocoagulation (CPC) on blood flow in the anterior segment of the eye. We show that laser CPC treatment applied to the rabbit eye provides a unique way to interrupt blood flow in the ciliary body, thus serving as a new method for evaluating clutter rejection performance in the microcirculation with and without an ultrasound contrast agent. We apply a recently developed eigendecomposition-based clutter rejection filter with modifications to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It is useful to note that the generation of subharmonic signals from contrast agents at conventional frequencies has been shown to be possible without the destruction of microbubbles [32]. In [17], [18] it was found that, at a 20-MHz transmit frequency, significant destruction of microbubbles did not occur until pressure levels much higher (>5 MPa) than those used in this study (1.8 MPa).…”
Section: A Performance Commentsmentioning
confidence: 77%
See 1 more Smart Citation
“…It is useful to note that the generation of subharmonic signals from contrast agents at conventional frequencies has been shown to be possible without the destruction of microbubbles [32]. In [17], [18] it was found that, at a 20-MHz transmit frequency, significant destruction of microbubbles did not occur until pressure levels much higher (>5 MPa) than those used in this study (1.8 MPa).…”
Section: A Performance Commentsmentioning
confidence: 77%
“…At present, work with microbubbles at high frequencies (>10 MHz) remains a relatively unexplored area in which virtually all studies have examined or assumed linear scattering [14], [15]. Initial studies have been conducted with microbubbles in high-frequency, pulsed-wave Doppler [16], [17] and color flow imaging [17], [18] experiments, which suggest the potential value of microbubbles for enhancing the signal strength from blood.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vivo studies have indicated the possibility of using UCAs with high-frequency systems to enhance detection of the vasculature. 30,31 Recently, Goertz et al 26,32 showed the feasibility of nonlinear high-frequency imaging with UCAs, but this approach requires extensive hardware modifications to detect the nonlinear characteristics of the UCAs, and commercialization of these prototypes is still under development.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission at such high frequencies also limits depth of penetration; and, when combined with attenuating media, very high pressures may be required to penetrate even 1 cm of tissue. Although contrast-assisted methods have demonstrated the ability to detect flow in subresolution vessels of the microcirculation [8], [13], [14], to the best of the authors' knowledge, no existing methods that take advantage of nonlinear UCA scattering have been demonstrated to resolve vessels on the scale of the microcirculation.…”
Section: Introductionmentioning
confidence: 99%